2021
DOI: 10.1371/journal.pone.0246886
|View full text |Cite
|
Sign up to set email alerts
|

Return and volatility transmission between oil price shocks and agricultural commodities

Abstract: This paper studies the connectedness between oil price shocks and agricultural commodities. Our sample period ranges from January 2002 to July 2020, covering the three global crises; Global Financial Crisis, the European sovereign debt crisis and Covid-19 pandemic crisis. We employ Granger causality tests, and the static and dynamic connectedness spillover index methodology. We find that the shocks in oil prices are Granger-caused mainly by price changes of grains, live cattle, and wheat, while supply shock gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 42 publications
6
35
0
1
Order By: Relevance
“…In addition, the linkage between crude oil and agricultural commodities increases significantly when financial crises and public health events occur, which is consistent with the findings of Umar, Gubareva, et al. (2021), Kumar et al. (2021), Balcilar et al.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the linkage between crude oil and agricultural commodities increases significantly when financial crises and public health events occur, which is consistent with the findings of Umar, Gubareva, et al. (2021), Kumar et al. (2021), Balcilar et al.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the supply shock of oil prices is mainly caused by price changes in grain (Umar et al., 2021). Shiferaw (2019) indicated that agricultural product prices and energy prices show a strong co‐movement.…”
Section: Introductionmentioning
confidence: 99%
“…In respect of the state of art relative to academic research on diverse financial and economic consequences of the pandemic, including design and implementation of policies facilitating recovery from the Covid-triggered slowdown, it is worth acknowledging that the respective literature has recently grown with a rapid pace ( [13][14][15][16][17][18][19][20]; and references therein). However, a major part of academic publications addressing the reaction of financial markets to the pandemic is mostly focused on the stock market impacts ( [3,5,8,9,21,22]; among others), commodities ( [23][24][25][26][27]; among others), currencies and crypto-currencies [28][29][30][31]. However, it is worth noting that the sovereign and corporate debt markets are barely addressed.…”
Section: Covid-19 Impact On Financial Marketsmentioning
confidence: 99%
“…Nevertheless, studies of this type are difficult to find, most of the research, in Europe, is focus on competitiveness of agricultural products [ 5 , 6 ], volatility of prices [ 7 ], sustainability of food system [ 8 ], the assessment of biological risk–diseases in animals [ 9 , 10 ], environmental risk [ 11 ], negative impacts of the agricultural commodities on ecosystems [ 12 ], and few analysis on commodities diversification and their impacts.…”
Section: Literature Review and Contextmentioning
confidence: 99%